Non-decimated Wavelet Transform for a Shift-invariant Analysis - Brassarote, G.o.n. [UNESP]; Souza, E.m.; Monico, J.f.g. [UNESP] (Sociedade Brasileira de Matemática Aplicada e Computacional, 2018)
Due to the ability of time-frequency location, the wavelet transform has been applied in several areas of research involving signal analysis and processing, often replacing the conventional Fourier transform. The discrete wavelet transform has great application potential, being an important tool in signal compression, signal and image processing, smoothing and de-noising data. It also presents advantages over the continuous version because of its easy implementation, good computational performance and perfect reconstruction of the signal upon inversion. Nevertheless, the downsampling required in the computation of the discrete wavelet transform makes it shift variant and not appropriated to some applications, such as for signals or time series analysis. On the other hand, the Non-Decimated Discrete Wavelet Transform is shift-invariant because it eliminates the downsampling and, consequently, is more appropriate for identifying both stationary and non-stationary behaviors in signals. However, the non-decimated wavelet transform has been underused in the literature. This paper intends to show the advantages of using the non-decimated wavelet transform in signal analysis. The main theoretical and practical aspects of the multi-scale analysis of time series from non-decimated wavelets in terms of its formulation using the same pyramidal algorithm of the decimated wavelet transform was presented. Finally, applications with a simulated and real time series compare the performance of the decimated and non-decimated wavelet transform, demonstrating the superiority of non-decimated one, mainly due to the shift-invariant analysis, patterns detection and more perfect reconstruction of a signal.

Devido sua habilidade de localização tempo-frequência, a Transformada wavelet tem sido aplicada em várias áreas de pesquisa envolvendo análise e processamento de dados, frequentemente substituindo a convencional Transformada de Fourier. A TransformadaWavelet Discreta tem um grande potencial de aplicação¸ destacando-se como uma importante ferramenta na compressão de sinal, processamento de imagem e sinal, suavização e filtragem de ruídos em dados. Ela também apresenta vantagens sobre a versão contínua por causa de sua fácil implementação, bom desempenho computacional e reconstrução perfeita do sinal após inversão. No entanto, a decimação requerida no cálculo da Transformada Wavelet Discreta a torna variante à translação e não apropriada para algumas aplicaões, tais como análise de sinais ou séries temporais. Por outro lado, a Transformada Wavelet Discreta Não Decimada é invariante à translação, porque elimina o processo de decimação, e consequentemente, é mais apropriada para identificar comportamentos estacionários e não estacionários presentes no sinal. No entanto, a Transformada Wavelet Não Decimada tem sido pouco usada na literatura. Esse artigo pretende mostrar as vantagens do uso na Transformada Wavelet Não Decimada na análise de sinais. Os principais aspectos teóricos e práticos da análise multiescala de séries temporais a partir das wavelets não decimadas, em termos de sua formulação usando o mesmo algoritmo piramidal da Transformada Wavelet Decimada, são apresentados. Por fim, aplicações com séries temporais simuladas e reais comparam o desempenho das transformadas wavelet decimada e não decimada, demonstrando a superioridade da wavelet não decimada, principalmente devido à análise invariante a translação, detecção de padrões e uma reconstrução mais perfeita do sinal.
Keywords: Non-decimated wavelets; shift invariance; time series; signal analysis; Wavelets não decimadas; invariância à translação; séries temporais; análise de sinais